MENINGOCOCCAL INFECTION IN CHILDREN IN KIROV REGION - T. V. Egorova; L. V. Malkova; I. P. Lushakova; O. L. Butorina; A. L. Stolbov (LLC "Diagnostics and Vaccines", 2015)
56 children aged 1 month to 17 years with generalized meningococcal infection were treated over the period 2004-2009. Antigens of meningococcus group B, C, Y/W 135 were isolated at the patients. The article siscusses clinical and laboratory features of infections caused by different groups of meningococcus.